Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Consider the following linear recurrence sequence.

$x_1 = 11$, $x_{n+1} = -0.8x_n + 9,\quad n = 1,2,3, \ldots.$

Find a closed form for this sequence.

share|cite|improve this question
What did you try? – Davide Giraudo Feb 1 '12 at 18:59
2… – yoyo Feb 1 '12 at 19:05
You should really try to write out the first few terms and see what happens if you have nowhere to go. – Patrick Da Silva Feb 1 '12 at 19:08

To get an idea of what the closed form might look like, let's iterate the relation a few times: $$ \begin{align} x_n &=9-.8x_{n-1}\\ &=9-.8(9-.8x_{n-2})\\ &=9-.8\cdot9+.8^2x_{n-2}\\ &=9-.8\cdot9+.8^2(9-.8x_{n-3})\\ &=9-.8\cdot9+.8^2\cdot9-.8^3x_{n-3}\tag{1} \end{align} $$ Looking at $(1)$, it appears that $$ x_n=9\frac{1-(-.8)^k}{1+.8}+(-.8)^kx_{n-k}\tag{2} $$ Equation $(2)$ can be verified using induction.

Verification: The case $k=1$ is just the given recursion: $x_n=9-.8x_{n-1}$.

Suppose $(2)$ is true for some $k$, then $$ \begin{align} x_n &=9\frac{1-(-.8)^k}{1+.8}+(-.8)^kx_{n-k}\\ &=9\frac{1-(-.8)^k}{1+.8}+(-.8)^k(9-.8x_{n-k-1})\\ &=9\frac{1-(-.8)^k}{1+.8}+9(-.8)^k+(-.8)^{k+1}x_{n-k-1}\\ &=9\frac{1-(-.8)^{k+1}}{1+.8}+(-.8)^{k+1}x_{n-k-1}\\ \end{align} $$ So $(2)$ is true for $k+1$.

Using $x_1=11$ and $k=n-1$, $(2)$ becomes $$ \begin{align} x_n &=5(1-(-.8)^{n-1})+(-.8)^{n-1}11\\ &=5+6(-.8)^{n-1}\tag{3} \end{align} $$

share|cite|improve this answer


if a=-5, this equation is equivalent to $x_{n+1}=-0.8x_n+9$

then we obtain:




share|cite|improve this answer

Use generating functions. Define $X(z) = \sum_{n \ge 0} x_{n + 1} z^n$, multiply the recurrence by $z^n$ and sum over $n \ge 0$ to get: $$ \frac{X(z) - x_1}{z} = - \frac{4 X(z)}{5} + \frac{9}{1 - z} $$ Thus: $$ X(z) = \frac{55 - 10 z}{5 - z - 4 z^2} = 5 \cdot \frac{1}{1 - z} + 6 \cdot \frac{1}{1 + 4 z / 5} $$ Two geometric series: $$ x_{n + 1} = 5 + 6 \cdot (-0.8)^n $$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.